Membangun Kesadaran Keislaman melalui Kegiatan Berbincang dengan Masyarakat Dusun Baturaja 3 - Putri Febriani; Soca Anggraini; Siti Zumrotus Sa’adah (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This study reports on an Independent Community Service Program (KKN Mandiri) conducted in Dusun Betu Raja 3, aimed at strengthening Islamic awareness through community-based educational activities. The program focused on two main initiatives: parenting dialogues with mothers, emphasizing child-rearing practices in line with Islamic values, and interactive sessions with children that introduced moral lessons from the stories of the prophets. Using participatory methods such as discussions, interactive lectures, and storytelling, the activities encouraged active engagement and created a supportive learning environment. Findings indicate that mothers gained a deeper understanding of the significance of Islamic parenting in shaping children’s moral character, while children demonstrated enthusiasm in listening to and applying the values embedded in prophetic stories. The program highlights the effectiveness of dialogical and narrative-based approaches in promoting religious awareness within rural communities. Overall, this initiative contributes not only to the development of individual family practices but also to the collective strengthening of Islamic identity in village life.